Collaboration Meeting with NCDCR - Nabilah Filzah, Mohd Radzuan (Faculty of Computing, 2021)
PEKAN, 6 July 2021- The collaboration meeting between FK and National Child Development Research Centre (NCDR) was held on 5 July 2021 virtually. The purpose was to discuss on data analytic project for KEMAS kids.